KAJIAN RESIKO PENDAPATAN USAHATANI JAGUNG DI DESA SABAH LIOH KECAMATAN BUNGA MAYANG KABUPATEN OGAN KOMERING ULU TIMUR (JASEP, 2015)
This study aimed to calculate income and analyze the risk of corn farming income in Sabah Lioh Village, Bunga Mayang Sub-district, Ogan Komering Ulu Timur Regency. The location is determined by purposive. The number of respondents is 30 corn farmers selected using simple random sampling. The result showed that corn farming income is Rp 7.150.560,50 per season. From risk analysis,the study finds that corn farming will not face risk significantly, which is indicated by the coefficient of variation of 0,09 with a lower limit value of the income is Rp 5.750.137,44.